Detraining increases body fat and weight and decreases VO2peak and metabolic rate - Ormsbee, M. J.; Arciero, P. J. (The Journal of Strength and Conditioning Research, 2012)
Competitive collegiate swimmers commonly take a month off from swim training after their last major competition. This abrupt cessation of intense physical training has not been well studied and may lead to physiopsychological decline. The purpose of this investigation was to examine the effects of swim detraining (DT) on body composition, aerobic fitness, resting metabolism, mood state, and blood lipids in collegiate swimmers. Eight healthy endurance-trained swimmers (VO2peak, 46.7 ± 10.8 ml/kg/min) performed 2 identical test days, 1 in the trained (TR) state and 1 in the detrained (~5 weeks) state (DT). Body composition and circumferences, maximal oxygen consumption (VO2peak), resting metabolism (RMR), blood lipids, and mood state were measured. After DT, body weight (TR, 68.9 ± 9.7 vs. DT, 69.8 ± 9.8 kg; p = 0.03), fat mass (TR, 14.7 ± 7.6 vs. DT, 16.5 ± 7.4 kg; p = 0.001), and waist circumference (TR, 72.7± 3.1 vs. DT, 73.8 ± 3.6 cm; p = 0.03) increased, whereas VO2peak (TR, 46.7 ± 10.8 vs. DT, 43.1 ± 10.3 ml/kg/min; p = 0.02) and RMR (TR, 1.34 ± 0.2 vs. DT, 1.25 ± 0.17 kcal/min; p = 0.008) decreased, and plasma triglycerides showed a trend to increase (p = 0.065). Our data suggest that DT after a competitive collegiate swim season adversely affects body composition, fitness, and metabolism. Athletes and coaches need to be aware of the negative consequences of detraining from swimming, and plan off-season training schedules accordingly to allow for adequate rest/recovery and prevent overuse injuries. It's equally important to mitigate the negative effects on body composition, aerobic fitness and metabolism so performance may continue to improve over the long term.